A New Instrumentation Amplifier Architecture Based on Differential Difference Amplifier for Biological Signal Processing - Zainul Abidin; Koichi Tanno; Shota Mago; Hiroki Tamura (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this paper, a new Instrumentation Amplifier (IA) architecture for biological signal pro-cessing is proposed. First stage of the proposed IA architecture consists of fully balance differential difference amplifier and three resistors. Its second stage was designed by using differential difference amplifier and two resistors. The second stage has smaller number of resistors than that of conventional one. The IA architectures are simulated and compared by using 1P 2M 0:6-m CMOS process. From HSPICE simulation result, lower common-mode voltage can be achieved by the proposed IA architecture. Average common-mode gain (Ac) of the proposed IA architecture is 31:26 dB lower than that of conventional one under 3% resistor mismatches condition. Therefore, the Ac of the proposed IA architecture is more insensitive to resistor mismatches and suitable for biological signal processing.